Fortifikasi NaFeEDTA pada cookies ubi jalar kuning sebagai produk alternatif untuk menanggulangi anemia defisiensi besi - Aulia, Salma Shafrina; Rustanti, Ninik; Fitranti, Deny Yudi (Jurnal Gizi dan Pangan, 2017)
The aims of the study were to analyze iron content, beta carotene content and organoleptic test of orange fleshed sweet potato cookies which had been fortified with NaFeEDTA. This reaserch used experimental method with one factor completely randomized design of iron with 100 ppm, 150 ppm and 200 ppm of NaFeEDTA. Analysis of iron content was conducted using Atomic Absorption Spectrophotometry and analysis of beta carotene was conducted by using spectrophotometry. Then, organoleptic test was conducted using hedonic test. The result of iron content in cookies is 27.97 ppm-53.42 ppm while beta caroten is 83.40 ppm-129.72 ppm. Organoleptic test results in terms of color, aroma, and texture, the fortified cookies were as well-liked as the control ones; taste, however, the panel found the fortified cookies more preferable. The highest level of iron content, beta carotene content and organoleptic test were orange fleshed sweet potato cookies fortified with 200 ppm NaFeEDTA.